Determinación del nivel de conocimiento sobre medidas antropométricas en estudiantes de primer a tercer año de la Escuela de Medicina del período lectivo 2010-2011 - Mejía Narváez, Victoria E. (2011)
The human body composition is now one of the most studied subjects, due to their unquestionable social importance and because it access different dimensions of physical body, plays an important role in disease diagnosis. Anthropometry is the study of body structure. Among the most important anthropometric measures we have the BMI and Waist and Hip Ratio and Waist Circumference.